TO STUDY THE EFFECT OF TRANSFORMATION IN ONLINE EDUCATION ON MENTAL HEALTH OF SOUTH ASIAN UNIVERSITIES IN THE CONTEXT OF INDIA, SRI LANKA AND NEPAL (BEFORE AND DURING COVID19) - Kumar, Mukesh; Hooda, Madhuri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The demand for quality education always creates new inventions and Massive Open Online Courses (MOOC) is one of that which is an online course with no limit of class size and provides free education via the web. In recent years, there has been an increasing interest in MOOCs as it provides a platform to large number of learners. No doubt, it enhanced the quality of education by including blended learning but it also affects the mental health of the students of universities. The main objective of this research paper is to study the mental health of students studying in South Asian Universities during Covid19. To achieve this objective, the investigator compared the scores of mental health of students of South Asian Universities before and during Covid19 in the context of India, Sri Lanka and Nepal. Descriptive research method was used in this research paper. 3000 students were selected randomly from different South Asian Universities. One self-made questionnaire of mental health was constructed by investigators to know the mental health of the students towards online education during Covid19. Question wise deep analysis of Mental Health of Students has also been done by the investigator and presented in the form of percentage. After analysis it was revealed that students felt anxiety, tension, depression, headache, tiredness and suffer eye problem in studying online mode during covid19. Finally, the investigator concluded that mental health of students of South Asian Universities was affected through transformation of online education during covid19.